IMF Survey, Volume 31, Issue 09. (IMF Survey; IMF Survey ;, 2002)
On September 1, 2001, Anne Krueger took up the reins as the IMF's First Deputy Managing Director. She brought with her a wealth of experience from the public and private sectors, including long stints in academia-most recently as an economics professor at Stanford University-and, from 1982 to 1986, as the World Bank's Vice President for Economics and Research. She is a Distinguished Fellow and past President ofthe American Economic Association.